2013
DOI: 10.1127/1863-9135/2013/0323
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Phormidium (Cyanobacteria, Oscillatoriales) from three Greek Caves: morphological and molecular analysis

Abstract: Specimens of cyanobacteria were collected from three geographically distant caves in Greece, and an interesting species of the Oscillatoriales was isolated and analyzed. Morphological characters were analyzed from fresh and cultured material using LM, SEM and TEM; moreover, molecular analysis based on the 16 S rRNA sequence was applied. This cyanobacterium bears a characteristic blackish, stratified, mucilaginous sheath and it is characterized by entangled filaments, facultative presence of false branching, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Cyanobacteria represent the first photosynthetic colonizers on the calcareous surfaces usually thriving both as epiliths and as endoliths (Lamprinou et al, 2009). Lamprinou et al (Lamprinou et al, 2013) observed predominance of Oscillatoriales group over Chroococcales in caves; our results show that also many Nostocales species form part of the cave communities, several of which, are understudied. For example, the Komarekiella sp.…”
Section: Biodiversitysupporting
confidence: 56%
“…Cyanobacteria represent the first photosynthetic colonizers on the calcareous surfaces usually thriving both as epiliths and as endoliths (Lamprinou et al, 2009). Lamprinou et al (Lamprinou et al, 2013) observed predominance of Oscillatoriales group over Chroococcales in caves; our results show that also many Nostocales species form part of the cave communities, several of which, are understudied. For example, the Komarekiella sp.…”
Section: Biodiversitysupporting
confidence: 56%
“…Although fewer strains were included, these two newly detected lineages were also indirectly found in previous investigations, most of which were ecological surveys of particular environments. A group corresponding to clade A is shown by Arp et al (2010) andTaton et al (2006a); highly supported clades equivalent to clade B are reported in De la Torre et al (2003), Lamprinou et al (2012b), Taton et al (2006b, Olsson-Francis et al (2010), andTaton et al (2011).…”
Section: Discussionmentioning
confidence: 85%
“…Black mold is a type of fungus and one of the most common culprits associated with the destruction of mortar and soft materials. In a less humid, semi-arid and arid environment, cyanobacteria, bacteria, algae and lichens are the primary groups responsible for material corrosion [ 14 ]. The microbes’ physical properties, as well as enzymatic biodeterioration, can cause damage and destroy artworks even those produced from modern materials such as polymer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%